Predicting heart failure events in patients with coronary heart disease and impaired glucose tolerance: insights from the Acarbose Cardiovascular Evaluation (ACE) trial - Wamil, M; McMurray, JJV; Scott, CAB; Coleman, RL; Sun, Y; Standl, E; Rydén, L; Holman, RR (Elsevier, 2020)
Aims: Heart failure is a fatal complication of type 2 diabetes but little is known about its incidence in people with impaired glucose tolerance (IGT). We used Acarbose Cardiovascular Evaluation (ACE) trial data to identify predictors of hospitalisation for heart failure (hHF) or cardiovascular (CV) death in patients with coronary heart disease (CHD) and IGT randomised to acarbose or placebo.